DETERMINANTS IN ACHICVING SUSTAINABLE PERFORMANCE OF VILLAGE-OWNED ENTERPISES - Satria Tri Nanda; Razana Juhaida Johari; Zuraidah Mohd Sanusi (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
Sustainable performance of village-owned enterprises, as one of the social enterprise organizations in Indonesia, has become the focus of various parties. This is because the performance of village-owned enterprises has not yet met expectations. Most village owned enterprises are inactive, and the rest barely survive in the villages. This study is an initial step to examine the factors that can influence the sustainable performance of village-owned enterprises. Based on previous literature and applicable regulations in Indonesia, this study suggests examining the impact of transformational leadership, organizational capability, good governance, and innovation on the sustainable performance of village-owned enterprises. This study also suggests exploring in-depth the measurement of sustainable performance in two dimensions, financial and social. Furthermore, for the future, measuring the good governance of village-owned enterprises can refer to the principles established in the regulations.